Impact of everolimus plus calcineurin inhibitor on formation of non-HLA antibodies and graft outcomes in kidney transplant recipients: 12-month results from the ATHENA substudy - Philippe, Aurélie; Arns, Wolfgang; Ditt, Vanessa; Hauser, Ingeborg A.; Thaiss, Friedrich; Sommerer, Claudia; Suwelack, Barbara; Dragun, Duska; Hillen, Jan; Schiedel, Christiane; Elsässer, Anja; Nashan, Björn (Frontiers in Transplantation, 2023)
Background Non-human leukocyte antigen (non-HLA) antibodies including antibodies targeting Angiotensin II type 1 (AT1R) and Endothelin-1 type A (ETAR) receptors represent a topic of interest in kidney transplantation (KTx). This exploratory substudy evaluated the impact of everolimus (EVR) or mycophenolic acid (MPA) in combination with tacrolimus (TAC) or cyclosporine A (CsA) in patients with preformed non-HLA antibodies, potentially associated rejections and/or their impact on renal function over 1 year. Methods All eligible patients were randomized (1:1:1) before transplantation to receive either EVR/TAC, EVR/CsA, or MPA/TAC regimen. The effect of these regimens on the formation of non-HLA antibodies within one year post de novo KTx and the association with clinical events was evaluated descriptively in randomized (n = 268) population. Results At Month 12, in EVR/TAC group, higher incidence of patients negative for AT1R- and ETAR-antibodies (82.2% and 76.7%, respectively) was noted, whereas the incidence of AT1R- and ETAR-antibodies positivity (28.1% and 34.7%, respectively) was higher in the MPA/TAC group. Non-HLA antibodies had no influence on clinical outcomes in any treatment group and no graft loss or death was reported. Conclusions The studied combinations of immunosuppressants were safe with no influence on clinical outcomes and suggested minimal exposure of calcineurin inhibitors for better patient management. Clinical Trial Registration https://clinicaltrials.gov/ (NCT01843348; EudraCT number: 2011-005238-21).